Behavior of an aluminum foam as an attenuator of electromagnetic radiation - Rodríguez-Méndez, Francisco (2019)
Electromagnetic interference affects the proper functioning of electronic devices. New cellular materials are showing their shielding potential from electromagnetic radiation interference due to their mechanical and energy absorption characteristics which, combined with a high electromagnetic wave reflection coefficient and good electrical conductivity, make them a useful material for this kind of application. The objective of this work is to analyze the behavior of an open cell metal foam as an attenuator of electromagnetic radiation by using computer simulation in ANSYS Electromagnetics. The physical system is modeled in a medium composed of air, with the selected material being aluminum; subsequently the system is subjected to dynamic electromagnetic fields produced by a linear antenna. The results obtained show that, from an incident magnetic and electric field of 1A/m and 5V/cm respectively, the behavior in magnitude of these fields is reduced as they enter the material matrix, down to values of 0.0691A/m for the magnetic field and 0.6573V/cm for the electric field.